P565 COVID-19 vaccination satisfaction and hesitancy in patients with inflammatory bowel disease: "inside referral center" survey. (21st January 2022) - Todeschini, A; Contaldo, A; Ierardi, E; Di Leo, A; Principi, M
Abstract: Background: Covid-19 infection is an exceptional pandemic that has involved millions of people worldwide with dramatic humane, social and economic concerns. Since December 2020, two mRNA and one inactivated vaccines were approved for people administration. The vaccinal access calendar was scheduled according with risk degree of infection and complications. In some regional setting patients with inflammatory bowel diseases (IBD), Crohn's disease (CD) and ulcerative colitis (UC) were considered fragile and therefore had a priority approach to vaccine administration compared to the general population. The purpose of this work was to measure the satisfaction and the concerns of a cohort of IBD patients who were administered the anti-Sars CoV-2 vaccine "inside reference center" by their dedicated nursing staff. Methods: Anti-SARS-CoV-2 vaccine (PfitzerÆ) in two shots were administrated to 346 IBD patients. Afterwards completed vaccination, all patients were given a questionnaire consisting of 4 items focused on the level of satisfaction and the impact of the pandemic on their illness. Results: 346 patients, 168 CD and 178 UC, 147 female and 199 male, 249 in biologicals and 97 in immunomodulatory therapy, regularly followed up in an IBD unit, were enrolled. All patients received two shots of SARS-CoV-2 vaccine by their IBD nursing staff. Upon close of the vaccination course, a questionnaire was dispensed. The pandemic did not affect IBD at all in 37.5% and a lot in 9.2% of participants. The majority (95%) of patients welcomed the possibility of getting vaccinated; only 7% feared the vaccine's influence on the course of the IBD. The main concerns were the possibility of adverse effects (33%) and the failure to achieve immunity (17%), few for the type of vaccine (3%) and the need for a further booster (6%). Almost all patients (99%) felt safer to have vaccinated at their IBD reference center. Conclusion: In this cohort of IBD patients, SARS-CoV-2 vaccination "inside reference center" has shown broad compliance and a high degree of confidence. Most did not report that the pandemic affected regular IBD management.